Stream of Consciousness Technique in (Azhdiha) Novel - Muhammad , Miran Jalal (Zanco Journal of Human Sciences, 2021)
The (Stream of consciousness) is considered as the most common and novel technique which to a larger extent is concerned with contemporary novel. It was first introduced through the (Ejdîha - Dragon) which belongs to (Muhammad Mukery). Since then, its characteristics have appeared in Kurdish Novel and its principles have been revitalized. Mukery in his novel embodied the characteristics and principles of this technique artistically and in a quite high level. He initially started narrating the process with a meticulous introduction to the events. He takes the receptors to the deep structure of the text and grabs his attention toward multiplicity of the consecutive events. In terms of the second forum and imagination dimensions of the novel, he gradually and comprehensively prompts to practicing the precise principles of (Stream of consciousness) in addition to paying a special attention to the sequences of the events and maintaining the elements of the text flavor. He, wisely in the frame of network narrating and in an interesting conclusion, joins both the imagination and the reality together and melts them with each other. The main significant reason of this favorable technique is that it leaves the receptors with eager and encourages him/her to interpret the events to reach a proper conclusion by themselves. This research is an attempt to highlight on the way of practicing the principle of the (Stram of consciousness) technique in the novel of (Dragon). It also introduces the role and value of the text to familiarize the most important and contemporary techniques of the novel with the genre of novel in Kurdish literature.